Application of Marine Plant Extract Powder (AMPEP) as a Nutrient Supplement for Optimizing Nannochloropsis sp. Cultivation - Sarri, Jurmin H.; Imlan, Khadiza H.; Ahajan, Nurmeta A.; Hairol, Melodina D.; Kissae, Al-Nasrif H.; Yangson, Nour Aley T.; Robles, Rizal Jhunn F.; Talaid, Emely M. (SAABRON PRESS, 2025)
Nannochloropsis sp. is a microalga widely recognized for its high nutritional content and potential in aquaculture, biofuel production, pharmaceuticals, and other biotechnological applications. This study investigated the effect of Acadian Marine Plant Extract Powder (AMPEP) as a nutrient enhancer at varying concentrations on the growth performance, pigment accumulation, and productivity of Nannochloropsis sp. Five experiments were established with AMPEP concentrations of 50, 100, 150, and 200 mg L⁻¹, alongside a control group without AMPEP. All experiments were conducted in triplicate. The results showed that cultures supplemented with 150 and 200 mg L⁻¹ AMPEP achieved significantly higher (p<0.05) cell densities after 21 days, recording 16.64 ± 2.10 × 10⁶ cells mL⁻¹ and 13.52 ± 2.65 × 10⁶ cells mL⁻¹, respectively, compared to the control (6.44 ± 0.50 × 10⁶ cells mL⁻¹). The highest specific growth rate (0.49 ± 0.12 day⁻¹) was observed at 150 mg L⁻¹ AMPEP as early as day 6, also significantly greater than that of the control group (0.13 ± 0.07 day⁻¹). The highest dry biomass was obtained at 50 mg L⁻¹ AMPEP and 100 mg L⁻¹ AMPEP concentration which is significantly higher (p<0.05) than that of the control experiment. Pigment analysis revealed that chlorophyll a and total carotenoids were significantly enhanced (p<0.05) at 150 and 200 mg L⁻¹ AMPEP compared to the control. These findings suggest that AMPEP can effectively promote the growth and pigment production of Nannochloropsis sp., making it a promising supplement for improving microalgal cultivation in biotechnological and aquaculture systems.